Human adipocyte function is impacted by mechanical cues - Pellegrinelli, V; Heuvingh, J; du Roure, O; Rouault, C; Devulder, A; Klein, C; Lacasa, M; Clément, E; Lacasa, D; Clément, K (The Journal of pathology, 2014)
Fibrosis is a hallmark of human white adipose tissue (WAT) during obesity‐induced chronic inflammation. The functional impact of increased interstitial fibrosis (peri‐adipocyte fibrosis) on adjacent adipocytes remains unknown. Here we developed a novel in vitro 3D culture system in which human adipocytes and decellularized material of adipose tissue (dMAT) from obese subjects are embedded in a peptide hydrogel. When cultured with dMAT, adipocytes showed decreased lipolysis and adipokine secretion and increased expression/production of cytokines (IL‐6, G‐CSF) and fibrotic mediators (LOXL2 and the matricellular proteins THSB2 and CTGF). Moreover, some alterations including lipolytic activity and fibro‐inflammation also occurred when the adipocyte/hydrogel culture was mechanically compressed. Notably, CTGF expression levels correlated with the amount of peri‐adipocyte fibrosis in WAT from obese individuals. Moreover, dMAT‐dependent CTGF promoter activity, which depends on β1‐integrin/cytoskeleton pathways, was enhanced in the presence of YAP, a mechanosensitive co‐activator of TEAD transcription factors. Mutation of TEAD binding sites abolished the dMAT‐induced promoter activity. In conclusion, fibrosis may negatively affect human adipocyte function via mechanosensitive molecules, in part stimulated by cell deformation. Published by John Wiley & Sons, Ltd